Application of Soft Bone Milkfish Processing Technology for Processed Fish SMEs in The City of Semarang - Sunyoto, Sunyoto; Saputro, Danang Dwi; Prasetyo, P. Eko; Ratnawati, Juli; Rachmadi, Moch Faizal (Pascasarjana Universitas Mataram, 2024)
Processed fish in the form of soft bone milkfish is a superior product of the city of Semarang that needs attention because it involves many business actors and has an influence on regional economic growth. However, there are still many obstacles related to production and marketing aspects. This paper is limited to handling production aspects in two fish processing SMEs in Semarang City, namely CV New Citra and UD Putri Laut. The problem faced by the two SME partners is that the production equipment for pressure cooking milkfish has a small capacity so that productivity is less than optimal. Another problem is that the shelf life of existing products is not long enough. To overcome this problem, the implementation team carries out community service using several methods, including socialization, training and mentoring. After the two tools were successfully created, the implementation team provided training and assistance on how to operate the two tools until the partners mastered and were skilled. Currently these two tools have been used in the pressure cooker milkfish production process, and have been proven to be able to increase production capacity and quality. Based on field observations, pressure cookers are able to increase production capacity by up to 300 percent, saving fuel costs by 66.66 percent. The retort tool succeeded in increasing product shelf life by up to 1 year, and saved retort costs of IDR 600,000, per retort process.